2020
DOI: 10.1042/cs20200477
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 and gut amino acid transport

Abstract: ACE2 is a type I membrane protein with extracellular carboxypeptidase activity displaying a broad tissue distribution with highest expression levels at the brush border membrane (BBM) of small intestine enterocytes and a lower expression in stomach and colon. In small intestinal mucosa, ACE2 mRNA expression appears to increase with age and to display higher levels in patients taking ACE-inhibitors (ACE-I). There, ACE2 protein heterodimerizes with the neutral amino acid transporter Broad neutral Amino acid Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 77 publications
0
81
0
Order By: Relevance
“…The presence of ACE2 on Type II cells specifically is very intriguing because these are the cells that 'taste' amino acids and ACE2 in the gut has been shown to dimerize with amino acid transporters where it plays a vital role in efficient amino acid absorption. 27 We hypothesize that ACE2 is also on the chemosensory cells present in airways as their cellular machinery is similar to Type II cells in taste buds. They contain bitter receptors activated by ligands such cycloheximide, a bitter receptor agonist, and require PLCβ 2 for signal transduction.…”
Section: Discussionmentioning
confidence: 90%
“…The presence of ACE2 on Type II cells specifically is very intriguing because these are the cells that 'taste' amino acids and ACE2 in the gut has been shown to dimerize with amino acid transporters where it plays a vital role in efficient amino acid absorption. 27 We hypothesize that ACE2 is also on the chemosensory cells present in airways as their cellular machinery is similar to Type II cells in taste buds. They contain bitter receptors activated by ligands such cycloheximide, a bitter receptor agonist, and require PLCβ 2 for signal transduction.…”
Section: Discussionmentioning
confidence: 90%
“…8a-b), as previously. Using these 2 assays, we observed that induction of both HNF1B and NFE2 improved viral entry, but not TP73 or SLC6A19, which was surprising for the latter as it is a known partner of ACE2 33 . In line with this, we observed that, despite differences in ACE2 levels in the 2 negative control cell lines, induction of HNF1B and NFE2 seemed to increase ACE2 expression, contrary to that of TP73 or SLC6A19 (Fig.…”
Section: Sars-cov-2 Production (Plaque Assays)mentioning
confidence: 86%
“…Assuringly, the top-scoring proviral (sensitization) hit was ACE2. Several solute carrier (SLC) transport channels also scored on this side of the screen, including SLC6A19 (rank 8), which is a known partner of ACE2 33 . Furthermore, SLC6A14 (rank 2) has been implicated in cystic fibrosis progression and shown to regulate the attachment of Pseudomonas to human bronchial epithelial cells 34 .…”
Section: Huh7mentioning
confidence: 99%
“…In the gut, ACE2 has a completely different function independent of RAS. ACE2 stabilizes neutral amino acid transporters, such as B0AT1 and loss of ACE2 compromises intestinal uptake of certain dietary amino acids, such as tryptophan[ 20 ]. Because tryptophan plays an important role in immunity, ACE2 knockout mice exhibited altered gut microbiota and developed more severe dextran sulfate sodium–induced colitis compared with wild-type control mice[ 21 ].…”
Section: Pathophysiological Mechanisms For Gi Symtoms In Covid-19mentioning
confidence: 99%